Re-Evaluating The Origins Of The European Union’s Emissions Trading Scheme: The Europeanisation Of Emissions Trading - Kelly, Gerard H. (Journal of Sustainable Development Law and Policy, 2025)
The adoption of carbon market trading in the European Union (EU) was far from assured. Prior to the Kyoto Protocol, the EU had been critical of market trading and had expressed grave reservations regarding its potential contribution to climate governance. Given this historical backdrop, the EU’s conversion to market trading and subsequent vocal championing of the merits of this regulatory approach, is particularly intriguing. Whilst emissions trading gradually garnered support within the EU, institutionally the Union remained trapped by the normative objections, which it had initially articulated against the idea. Such norm entrapment – the inability to pursue a preferred policy that violates a norm because of prior rhetorical affirmation of the norm – presented a particular dilemma for the EU. Paradoxically, the contribution of individual norm entrepreneurs, located within the Commission, in reframing emissions trading as an effective and efficient instrument for climate governance in the EU proved considerable to unlocking this entrapment dilemma. As a result, a concept, which the EU had previously delegitimised as evasive of domestic responsibilities, was instead reconstructed as a legitimate strategy to salvage the Kyoto Protocol. As market trading internationalises, understanding the drivers and processes by which the EU ETS came to occupy the cornerstone of EU climate policy may offer valuable insights to policy-makers and stakeholders endeavouring to promote global emissions trading initiatives.